2020
DOI: 10.1097/md.0000000000022551
|View full text |Cite
|
Sign up to set email alerts
|

A second C-reactive protein (CRP) test to detect inflammatory burst in patients with acute bacterial infections presenting with a first relatively low CRP

Abstract: A first C-reactive protein (CRP) test, as often performed by clinicians during the presentation of patients with an acute bacterial infection, might be misleading. The aim of our study was to explore the dynamic between a second CRP test taken within 12 hours from admission CRP test in a cohort of patients diagnosed with acute bacterial infection in comparison to CRP in a control group of apparently healthy individuals. This was a historical cohort study comprised of all patients admitted to the Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Importantly, a certain threshold of CRP must be reached to significantly elevate deposition of C3, as evidenced by ELISA assays (Figures 2A, B) and the fact that we could not see this effect on glomerular endothelial cells when patient serum containing 22.6 mg/ml was used. However, the CRP concentration of 150 mg/ml used in the immunofluorescence imaging and flow cytometry experiments is not unusual and can be achieved in case of infections but also non-infectious inflammatory lesions, as reported in (24)(25)(26)(27). Another lesson from our experiments is that the GoF phenotype of both C2 variants can be observed when CRP but not human immunoglobulins are coated on ELISA plates (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a certain threshold of CRP must be reached to significantly elevate deposition of C3, as evidenced by ELISA assays (Figures 2A, B) and the fact that we could not see this effect on glomerular endothelial cells when patient serum containing 22.6 mg/ml was used. However, the CRP concentration of 150 mg/ml used in the immunofluorescence imaging and flow cytometry experiments is not unusual and can be achieved in case of infections but also non-infectious inflammatory lesions, as reported in (24)(25)(26)(27). Another lesson from our experiments is that the GoF phenotype of both C2 variants can be observed when CRP but not human immunoglobulins are coated on ELISA plates (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The level of CRP is usually low in healthy individuals but can elevate 100- to 200-fold or higher in acute systemic inflammation [ 12 ] and is chronically elevated in patients with T2DM. In individuals with T2DM, CRP levels range between 4.49 and 16.48 mg/L [ 13 , 14 ] and among individuals with acute systemic inflammatory response syndromes from 31.08 [ 15 ] to 226.1 mg/L [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that patients who are admitted with very low CRP concentrations do not necessarily present a benign course of their disease [ 3 ]. In addition, we could show that a follow-up CRP test could add significant prognostic information to the medical team [ 4 , 5 , 6 , 7 , 8 ]. In fact, a second CRP test could single out those individuals who are at an increased risk of death during hospitalization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%